Effectiveness of Group Counseling with Mindful Breathing Technique in Reducing Student Anxiety - Sakina Rasido; Dhevy Puswiartika; Ikhlas Rasido; Hasan Hasan (MASI Mandiri Edukasi, 2026)
Adolescent anxiety is a growing mental health concern, with prevalence reaching 3.7% in Indonesia, yet practical and effective school-based interventions remain limited. This study aims to examine the effectiveness of group counseling with the mindful breathing technique in reducing anxiety among students at SMA Model Terpadu Madani Palu. An experimental method with a Pretest-Posttest Control Group Design was employed, involving 20 students selected through purposive sampling, divided into an experimental group (n=10) and a control group (n=10). Anxiety levels were measured using the Social Anxiety Scale for Adolescents (SAS-A), comprising 18 valid items (α=0.731). Data were analyzed using Paired Sample t-tests and Mann-Whitney U tests in SPSS. Results showed a significant reduction in anxiety in the experimental group (t=6.444, p=0.000, Cohen’s d=2.04), with 60% of students reaching the low-anxiety category after six intervention sessions, compared to none prior to the intervention. The Mann-Whitney U test confirmed a significant difference between groups (p=0.000). These findings demonstrate that group counseling integrated with the mindful breathing technique is an effective, accessible, and practical strategy for reducing student anxiety in school settings.